COCOYAM. Establishing alliances to develop the cocoyam (Xanthosoma sagittifolium) value chain - Valle Martínez, Edwin José; Rizo Picado, Aileen Ivania; Rocha Albuquerque, José Alfredo; Picado Vanegas, Armando; Laguna González, Tomás Javier (Catholic Relief Services, 2012)
This publication is the result of a participatory experience capitalization, facilitated by the International Center for Tropical Agriculture for the project “Alliance to Create Opportunities for Rural Development through Agro-enterprise Relationships” (ACORDAR). This report addresses the process of establishing and strengthening the cocoyam value chain through innovations implemented at different stages. Highlights are (i) the important learning process that occurred at different stages of construction of the value chain; (ii) the results obtained by the collective action of Alliance actors; and (iii) the lessons learned throughout the process, which serve as basis for decisionmaking tools in future initiatives.